Implementation of the Simple Additive Weighting Method to Select Tourist Attractions in Jayapura City - Reski; Pawan, Elvis; Hasan, Patmawati (International Journal of Applied Research and Sustainable Sciences, 2024)
The study explores the implementation of the Simple Additive Weighting (SAW) method for the selection of the best tourist attractions in Jayapura City. The SAW method is used to calculate the tourist attraction rating based on the criteria that have been established. The study aims to provide recommendations for the best tourist attractions for travelers visiting Jayapura City. Data on various tourist attractions and relevant criteria are collected, then analyzed using the SAW method. The results of research show that the SAW method can be effectively used in selecting the best tourist attraction, helping tourists make better and more satisfactory decisions. Target the test results of the system to the test accuracy level based on a 100% blackbox method, which means the system can be implemented